Necrotising fasciitis: clinical judgement and early multidisciplinary collaboration is the key. (18th October 2021) - Hosty, Jennifer; Cheema, Ali; Magdum, Ashish A
Abstract: Necrotising fasciitis is a bacterial infection of subcutaneous tissue and fascia, which can rapidly progress to septic shock. Diagnosis is frequently delayed or missed due to non-specific presentation. The laboratory risk indicator for necrotising fasciitis (LRINEC) stratifies risk based on biochemical results, but external validation revealed limited accuracy. A 78-year-old female with significant co-morbidities presented with right foot pain and erythema. Vital signs were normal and C-reactive protein was 18 mg/l. LNIREC was 0. She was treated for cellulitis, but within 24 h developed skin blistering and necrosis. After consideration of risks, washout and debridement was performed under popliteal block. Recovery was prolonged and complicated by nosocomial infection. This case highlights the importance of clinical suspicion for necrotising fasciitis and the complexity of management decisions considering recovery can be protracted.